Analisis Kemampuan Berpikir Kreatif Matematis Berdasarkan Tingkat Kecemasan Matematis Siswa pada Materi Lingkaran - Julianti Anggraeni (Departement of Mathematics Education, 2024)
The aim of this research is to describe creative mathematical thinking abilities in terms of the level of mathematical anxiety of students in class VIII SMP IT Addzimat Da'i Indonesia. The research subjects were 44 students in class VIII A and VIII B for the 2023/2024 academic year. The data collected was in the form of test results on students' ability to understand mathematical creative thinking abilities and non-test results regarding mathematical anxiety. The test questions used to measure students' ability to understand mathematical creative thinking skills consist of 3 questions in the form of essays with circle material. The results of data analysis show that students' ability to understand mathematical creative thinking skills is still relatively low and students' levels of mathematical anxiety are high as evidenced by the percentage of achievement of each indicator. This research aims to find out how the results of creative mathematical thinking skills in circle material are in terms of the level of mathematical anxiety of students at SMP IT Addzimat Da'i Indonesia Rancaekek class VIII.